Factors Contributing to Retention in Care and Treatment Adherence Among People Living With HIV Returning to Care in South-Eastern Tanzania: A Qualitative Study - Matimbwa H; Lolo SA; Matoy LS; Ndaki R; Ngahyoma S; Mollel HA; Luoga E; Vanobberghen F; Vianney JM; Idindili B; Weisser M (HIV/AIDS: Research and Palliative Care)
Hassan Matimbwa,1– 3 Sarah Andrea Lolo,1,2,4 Leila S Matoy,1,2 Regina Ndaki,1 Suzan Ngahyoma,5,6 Henry Abraham Mollel,7 Ezekiel Luoga,1,5 Fiona Vanobberghen,8,9 John-Mary Vianney,2 Boniphance Idindili,10 Maja Weisser,1,8,11 The Kilombero and Ulanga Antiretroviral Cohort study group (KIULARCO)Kabula Aaroni1. 1, Aschola Asantiel1. 1, Farida Bani1. 1, Theonestina Byakuzana1. 1, Joyce Claud1. 1, Adolphina Chale1. 1, Elizabeth Dotto1. 1, Gideon Francis3. 310. 1011. 11, Tracy Glass4. 45. 5, Yvonne Haridas1. 1, Jerry Hella1. 1, Speciosa Hwaya3. 3, Rodney Julius1. 1, Aneth V Kalinjuma1. 16. 67. 7, Andrew Katende1. 1, Yassin Kisunga1. 1, Ezekiel Luoga1. 1, Jerome Lwali1. 18. 89. 9, Edgar Enzigard Martin1. 1, Honorati Masanja1. 1, Swalehe Masoud1. 1, Mohammed Mbaruku1. 1, George Mfanando1. 1, Josephine Mhina1. 1, Mengi Mkulila3. 3, Margareth Mkusa3. 310. 1011. 11, Fransisca Alfred Mmbando1. 1, Lina Mnunga3. 310. 1011. 11, Alpha Mninje3. 310. 1011. 11, Dorcas K Mnzava1. 1, Getrud J Mollel1. 1, Lilian Moshi1. 1, Germana Mossad3. 310. 1011. 11, Rejina Mponji3. 310. 1011. 11, Dolores Mpundunga3. 3, Athumani Mtandanguo1. 1, Ummu-kulthum Mwaliga11. 1, Selerine Myeya1. 1, Sanula Nahota1. 1, Sharifa Nakapala3. 310. 1011. 11, Regina Ndaki1. 1, Robert C. Ndege1. 1, Agatha Ngulukila1. 1, Alex John Ntamatungiro1. 16. 67. 7, Vaileth Nyaenza3. 310. 1011. 11, Emmanuel Nyenza1. 1, Amina Nyuri1. 1, James Okuma4. 45. 5, Ally Olotu1. 1, Daniel H Paris4. 45. 5, Martin Rohacek1. 14. 45. 5, Leila Samson1. 1, Elizabeth Senkoro1. 1, George Sigalla1. 1, Joseph Singo1. 1, Jamali B Siru1. 1, Jenifa Tarimo1. 1, Albart R Malabe3. 310. 1011. 11, Juerg Utzinger4. 45. 5, Fiona Vanobberghen4. 45. 5, Maja Weisser1. 14. 45. 510. 10, John Wigay1. 1, Lulu Wilson1. 1 On behalf of the KIULARCO Study Group1Interventions and Clinical Trials Department, Ifakara Health Institute, Morogoro, Tanzania; 2School of Life Science and Bioengineering, The Nelson Mandela African Institute of Science and Technology, Tengeru, Arusha, Tanzania; 3Department of Health Services, Mzumbe University, Mbeya, Tanzania; 4Department of Secondary Education, Singida, Tanzania; 5Chronic Disease of Ifakara, St. Francis Regional Referral Hospital, Morogoro, Tanzania; 6Benjamin Mkapa Foundation, Dar Es Salaam, Tanzania; 7Department of Health Systems Management, Mzumbe University, Morogoro, Tanzania; 8Swiss Tropical and Public Health Institute, Allschwil, 4123, Switzerland; 9University of Basel, Basel, 4002, Switzerland; 10Public Health Department, The Kampala International University, Dar Es Salaam, Tanzania; 11Division of Infectious Diseases, University Hospital Basel, Basel, 4031, Switzerland; 1.Ifakara Health Institute, Ifakara, Tanzania; 2.University Hospital Basel, Basel, Switzerland; 3.Saint Francis Referral Hospital, Ifakara, Tanzania; 4.Swiss Tropical and Public Health Institute, Allschwil, Switzerland; 5.University of Basel, Basel, Switzerland; 6.Epidemiology and Biostatistics Department, School of Public Health, Faculty of Health Sciences, University of the Witwatersrand; 7.Division of Public Health, School of Public Health and Family Medicine, University of Cape Town, South Africa; 8.Indiana University, Indianapolis, U.S.; 9.Division of Infectious Diseases and Hospital Epidemiology, University Hospital Basel, University of Basel, Switzerland; 10.Benjamin Mkapa Foundation, Dar es Salaam, Tanzania; 11.USAID Afya Yangu, Dar es Salaam, TanzaniaCorrespondence: Hassan Matimbwa, Ifakara Health Institute, P.O. Box 53, Off Mlabani Passage, Ifakara, Morogoro, Tanzania, Tel +255 718 371 666, Email hassanmatimbwa@gmail.comBackground: People living with HIV (PLHIV) with good adherence to antiretroviral therapy (ART) achieve good health outcomes. However, treatment interruptions remain a major challenge, particularly in rural Africa. This study explored factors related to dropout, return, retention in care, and treatment adherence among PLHIV returning to care after missing clinical visits.Methods: We conducted an exploratory study using a phenomenological approach in rural South-eastern Tanzania, from July to October 2023. In-depth interviews (IDIs) were conducted with 21 PLHIV who resumed care after missing visits for three months or more from the last scheduled appointment and who were taking ART less than 60 days within the last three months, and their 13 treatment supporters. Interviews were conducted at St. Francis Regional Referral Hospital and Kibaoni Health Center.Five focus group discussions (FGDs) were conducted with 6– 8 healthcare workers from Kibaoni, Mang’ula, Mkamba, Mgeta Health Center, and St. Francis Hospital. Data were analyzed by thematic analysis, with NVivo 12 software.Results: The median age of the 21 PLHIV was 40 years (range 21 to 63); 10 (47.6%) were females. Reasons for dropping out of care reported included fear of disclosure, complacency with improved health, denial of HIV status, work-related absence, and religious beliefs. Reasons for returning included health deterioration, completion of work obligations causing care interruption, family support, and clinic follow up. Factors promoting retention and adherence were improved health through ART, trust in healthcare services, counseling, health education, clinic follow-up, longer drug refill periods, and family support.Conclusion: Our study highlights persisting stigmatization contributing to dropping from care, with strong family and social support improving adherence and clinic attendance. Future interventions should focus on these factors to enhance retention of lifelong treatment adherence. Working obligations remain a challenge, that could be addressed by facilitated access to remote drug pickup.Keywords: attrition from care, retention in HIV care, treatment adherence, people living with HIV, South-Eastern Tanzania